Violence in the courtship and their relationship with the passive emotional dependence in university students - Del Castillo Arreola, Arturo (Consorcio de Universidades Mexicanas A.C., 2015)
The courtship is a stage where people have the opportunity to meet each other, to learn how to share, to identify similarities and, inclusive, to detect symptoms of dating violence in the long term relationship. These last they can increase in frequency and intensity with the step of the time, until it represents a precedent of the domestic violence. Previous studies refer that the presence of separation anxiety as a sing of emotional dependency and deficiency is some factor that is associated with the genesis of dating violence. The objective of the present study was to identify the relationship between the factors of emotional dependence and violence in the courtship among university students. The sample included 317 doctor, administration and law students of the University of the State of Hidalgo. It was used the Emotional Dependence Questionnaire and Dating Violence Questionnaire, to evaluate the mentioned variables. Pearson correlation analysis was used, obtaining statistically significant positive relations between the separation anxiety and border expression factors of the Emotional Dependency questionnaire and the emotional blackmail, control and jealous factors of the dating violence questionnaire. Based on these results, psychological interventions could be planned with the objective of developing social skills that facilitate the independency and improvement of interpersonal relationships.